Relationship between Level of Test Anxiety and Module Score in Medical Students: An Analytical Observational Study - Aryati, Salsabila; Hastuti, Rizkie Woro; Soetoko, Anita Soraya (Universitas Islam Sultan Agung, 2024)
Modul score are scores obtained from theoretical exams in the form of MCQ (Multiple Choice Questions) which have a large portion in determining graduation. The achievement of module scores can be influenced by many factors, one of which is the level of anxiety. Anxiety during exams is known to inhibit cognitive function which affects performance during exams so that it can affect the results obtained. This study aims to determine the relationship between the level of anxiety and the value of the mental health problem module in FK Unissula students class of 2021. This study is an observational study with a cross-sectional research design conducted at the Faculty of Medicine, Universitas Islam Sultan Agung. Respondents were asked to complete the Nist and Diehl Test Anxiety Questionnaire questionnaire consisting of 10 questions. The data obtained were analyzed with the spearman correlative test to determine the meaning and strength of the relationship between anxiety levels and module scores. The results of the study from 140 samples found that most students who were not anxious got good grades with a percentage of 63.1%, students who were mildly anxious the majority got enough scores with a percentage of 36.2% and students who were severe anxious about the majority got less scores with a percentage of 56%. The results of the bivariate analysis test using the spearman correlative test obtained a p value of 0.000 (p < 0.05). The correlation coefficient between anxiety levels and module scores was 0.391. The level of anxiety significantly affects the value of the mental health problem module in FK UNISSULA students batch 2021 with weak correlation strength.